Right ventricular papillary muscle approximation for functional tricuspid regurgitation associated with severe leaflet tethering. (15th December 2017) - Matsumiya, Goro; Kohno, Hiroki; Matsuura, Kaoru; Sakata, Tomoki; Tamura, Yusaku; Watanabe, Michiko; Ueda, Hideki
Abstract: Recurrent tricuspid regurgitation (TR) can occur after tricuspid annuloplasty if severe leaflet tethering persists. To reduce the tethering, we applied right ventricular papillary muscle approximation in 7 patients with severe functional TR associated with significant leaflet tethering. Postoperative echocardiogram revealed mild or less TR and a significant reduction in the tethering effect. In conclusion, this adjunctive technique can improve functional TR associated with leaflet tethering.